Highly soluble tetra lauryl alcohol substituted phthalocyanines; synthesis, electrochemistry, spectroelectrochemistry - KOCA, ATIF (TAYLOR & FRANCIS LTD, 2015)
The tetra peripherally -substituted 2(3),9(10),16(17),23(24)-tetrakis undecyloxy phthalocyanine derivatives, M{Pc[O-(CH2)(11)CH3)](4)} Pc: Phthalocyanine, [M: Zn(II)(2), Ga(III)(3), and Ti(IV)(4)], have been synthesized and characterized using FT-IR, H-1, and (CNMR)-C-13, MS(MALDI-TOF), UV-vis, atomic force microscopy, electro and spectroelectro chemical and elemental analysis. The new synthesized complexes are soluble in both polar solvents and nonpolar solvents, such as THF, DMF, CHCl3, CH2Cl2, benzene, and even hexane. Electrochemical and spectroelectrochemical measurements give common metal-based and/or Pc ring-based redox processes which support the proposed structures of the complexes. While titanium phthalocyanine exhibits metal- and Pc ring-based reduction and/or oxidation couples, gallium and zinc phthalocyanines give only Pc ring-based electron transfer processes.
Keywords: Phthalocyanine; Zinc; Gallium and Titanium; Synthesis; Spectroelectrochemistry; Electrocolorimetry; RECEPTOR FUNCTIONAL PHTHALOCYANINES; METAL-ION BINDING; COMPLEXES; ALPHA; POSITIONS; CO(II)